Calculated Versus Estimated Blood Loss in Plastic Breast Surgery - Carly M. Wareham, MD; Gabriel De La Cruz Ku, MD; Manish M. Karamchandani, MD; Abhishek Chatterjee, MD, MBA, FACS; Sarah M. Persing, MD, MPH; Christopher Homsy, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Estimated blood loss (EBL), based on surgeons’ visual estimation of blood loss, guides patient care but is often inaccurate. Calculated blood loss (CBL), a measurement of the volume of blood lost, is a more accurate substitute. Our aim was to assess the differences between EBL and CBL in plastic surgery. Methods:. A retrospective analysis was conducted on 35 patients who underwent deep inferior epigastric perforator flaps, oncoplastic surgery, breast reductions, or mastectomies in 1 hospital over 18 months. Results:. The surgeons underestimated EBL (median EBL 250 versus CBL 388 cc, P < 0.001). EBL and CBL from surgeon 2, a senior surgeon, were not statistically different compared with those of surgeon 1 (250 versus 250 cc, P = 0.958; 363 versus 501 cc, P = 0.143), but tended to have less delta EBL–CBL (113 versus 273 cc, P = 0.066). Both breast reductions/mastectomies and deep inferior epigastric perforators had higher CBL (200 versus 360 cc, P < 0.001; 300 versus 748 cc, P = 0.015), but less delta EBL–CBL (116 versus 438 cc, P = 0.054). There was a strong negative relationship between EBL and postoperative hemoglobin, and a moderate relationship between CBL and delta EBL–CBL with case duration, intraoperative fluids, and urine output. Conclusions:. The surgeons underestimate blood loss, but the senior surgeon tended to do so to a lesser extent. Complex and longer procedures tended to have a greater discrepancy between EBL and CBL. CBL should be considered as a reliable alternative to EBL.